2023
DOI: 10.1007/s10098-023-02469-4
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of novel ZnO nanoparticles for efficient photodegradation of industrial dyes

Abstract: The removal of persistent dye pollutants from wastewater streams has drawn a lot of interest from the scienti c community because photocatalysis is the most widely used practical strategy for addressing environmental contamination. Transition-metal oxides are seen to be the most prospective catalysts for e cient and environmental friendly wastewater treatment because of their signi cant photocatalytic activity, excellent solubility, and durability. In this study, we describe the simple, eco-sustainable and cos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Figures 2A,B show the surface morphologies of the Semal-ZnO NPs under different magnifications; the SEM images show that most of the Semal-ZnO NPs are spherical and have a synthesized diameter range of 5–35 nm. The green Semal-ZnO NPs are also found to be aggregated and homogeneous owing to the stacking morphology ( Abdelbaky et al, 2022 ; Purkait et al, 2023 ; Sreelekshmi et al, 2023 ; Supin et al, 2023 ). The agglomerated particles indicate larger sizes with low surface-to-volume ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 2A,B show the surface morphologies of the Semal-ZnO NPs under different magnifications; the SEM images show that most of the Semal-ZnO NPs are spherical and have a synthesized diameter range of 5–35 nm. The green Semal-ZnO NPs are also found to be aggregated and homogeneous owing to the stacking morphology ( Abdelbaky et al, 2022 ; Purkait et al, 2023 ; Sreelekshmi et al, 2023 ; Supin et al, 2023 ). The agglomerated particles indicate larger sizes with low surface-to-volume ratios.…”
Section: Resultsmentioning
confidence: 99%
“…1-079-2205), which was used as the reference with lattice parameters a = 3.2501 A and c = 5.2071 A using X'Pert HighScore Plus software (Figure 1B) (Abdelbaky et al, 2022;Chandrasekaran et al, 2023). The diffraction pattern revealed that all samples were in the same position and that no additional peaks of any alternative species were found, proving that all of the precursors were completely decomposed during the process (Figure 1B) (Sreelekshmi et al, 2023). The results also demonstrated that diffraction peaks corresponding to impurities were absent in the PXRD patterns, confirming the high purity of the synthesized Semal-ZnO NPs (Meena et al, 2023;Mishra et al, 2023).…”
Section: Pxrd Patternsmentioning
confidence: 98%
“…However, these physicochemical methods, though some are technically viable, are accompanied with the use of hazardous chemicals, high-energy, long-time consumption and high cost. Alternatively, green synthesis of NPs has gained wide interest because of its low cost, low toxicity and eco-friendly nature [ 22 , 23 ]. Using plant extracts offers a green and sustainable opportunity for exploring the biosynthesis of ZnO NPs and is both more environmentally benign and more rapidly progressive than conventional chemical methods [ 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic way of organic pollutant removal is one of the most used ways and this process produces no secondary pollutants. There are different types of photo-catalysts such as TiO 2 [ 11 ], g-C 3 N 4 /TiO 2 [ 12 ], TiO 2 -WO 3 Nanocomposite [ 13 ], hydroxyapatite [ 14 ], ZnCoO [ 15 ], ZnFe 2 O 4 [ 16 ], ZnO [ 17 ], spinel ferrites/metal oxide nanocomposites [ 18 ] etc. There remains a cost associated with the catalyst which ultimately enhances the total cost of the wastewater treatment process.…”
Section: Introductionmentioning
confidence: 99%